Responsibility and Character Education Based on School Culture - Setiyono Setiyono; Yessica Al Fawzia (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this research was to describe and analyze the planning, implementation, and evaluation of responsible character education based on school culture. A qualitative approach is taken in this investigation. An SMP Muhammadiyah Plus Salatiga sample was used in the analysis. In order to gather accurate information about the subject matter, the authors employ qualitative research methods, such as interviews and documentation. There are two ways to implement educational character education in the classroom: first, incorporate it into the school's curricula and rules, then spread the word to the students and staff. Character education for responsibility is carried out by incorporating the character of responsibility into self-development programs, subjects, and school culture. 2. This includes classroom and school-wide activities in which character values are taught and practiced. Students' attitudes are assessed as a means of evaluating responsibility character education.